Advances in Peptide and Peptidomimetic Design Inspiring Basic Science and Drug Discovery: A Themed Issue Honoring Professor Victor J. Hruby on the Occasion of His 80th Birthday - Sawyer, Tomi; Haskell-Luevano, Carrie; Mosberg, Henry (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Advances in Peptide and Peptidomimetic Design Inspiring Basic Science and Drug Discovery is a book dedicated to Prof. Victor J. Hruby on the occasion of his 80th birthday. This book includes twenty contributions from authors representing diverse multidisciplinary fields of scientific expertise, and is focused on the extraordinary potential of peptides and peptidomimetics as a surging therapeutic modality and as tools for basic research and technology development.